On $(Φ , m)$-homoderivations in Rings (European Journal of Pure and Applied Mathematics, 2025)
In this article, we examine the commutativity of a ring $Ω$ endowed with a specific kind of mappings called centrally extended $(Φ, m)$-homoderivations, where $Φ$ is a mapping on $Ω$, and $m$ is an integer. This mapping is a comprehensive kind of the homoderivation, $Φ- $homoderivation, and $ m $-homoderivation. Besides, we provide some properties of its center.
Keywords: Prime and semiprime Rings; Homoderivation; $CE-$derivation